Creating a compassion system to achieve efficiency and quality in health care delivery. (1st January 2021) - Vogus, Timothy J.; McClelland, Laura E.; Lee, Yuna S.H.; McFadden, Kathleen L.; Hu, Xinyu
Abstract : Purpose: Health care delivery is experiencing a multi-faceted epidemic of suffering among patients and care providers. Compassion is defined as noticing, feeling and responding to suffering. However, compassion is typically seen as an individual rather than a more systemic response to suffering and cannot match the scale of the problem as a result. The authors develop a model of a compassion system and details its antecedents (leader behaviors and a compassionate human resource (HR) bundle), its climate or the extent that the organization values, supports and rewards expression of compassion and the behaviors and practices through which it is enacted (standardization and customization) and its effects on efficiently reducing suffering and delivering high quality care. Design/methodology/approach: This paper uses a conceptual approach that synthesizes the literature in health services, HR management, organizational behavior and service operations to develop a new conceptual model. Findings: The paper makes three key contributions. First, the authors theorize the central importance of compassion and a collective commitment to compassion (compassion system) to reducing pervasive patient and care provider suffering in health care. Second, the authors develop a model of an organizational compassion system that details its antecedents of leader behaviors and values as well as a compassionate HR bundle. Third, the authors theorize how compassion climate enhances collective employee well-being and increases standardization and customization behaviors that reduce suffering through more efficient and higher quality care, respectively. Originality/value: This paper develops a novel model of how health care organizations can simultaneously achieve efficiency and quality through a compassion system. Specific leader behaviors and practices that enable compassion climate and the processes through which it achieves efficiency and quality are detailed. Future directions for how other service organizations can replicate a compassion system are discussed.